Determination of minority carrier diffusion lengths in semiconductor wafers with non-uniform carrier lifetimes by the surface photovoltage technique - Tan, L.S. (2014)
Conference on Optoelectronic and Microelectronic Materials and Devices, Proceedings, COMMAD